Scalable and Socially Inspired Blockchain Architecture for the Organic Food Supply Chain - Thanushya Thanujan; Chathura Rajapaksha; D.N. Wickramarachchi (Journal of Innovation Information Technology and Application (JINITA), 2022)
Organic food supply chains are faced with heavy pressure to increase their output to meet the global demand. This confronts various challenges including scandals, adulteration, contamination, and growing regulations. As an alternative to third-party certification, Participatory Guarantee Systems (PGS) are popular community-based quality assurance system that integrates the social verification context into the organic certification process. As PGS is a local community-driven system, it has inherent limitations in the scalability of reaching consensus as the size of participants increases. The organic food industry has the potential to grow globally therefore, an appropriate scalable consensus mechanism is needed to deal with community-level consensus as an alternative to the existing PGS system. Blockchain architecture with hybrid consensus mechanisms seems to be the potential solution to address the trust and scalability issues in the organic food supply chain. This paper proposes a socially inspired hybrid blockchain architecture for the organic food supply chain to address the scalability issues via hybridizing two consensuses’ mechanisms with the combined advantages of Proof of Authority (PoA) and Federated Byzantine Agreement (FBA). In the proposed architecture, much eminent aspect of community-level trust is integrated into the consensus process. Furthermore, this paper presents a concept-level validation as a qualitative analysis of the proposed architecture based on experts’ opinions. Concept-level validation of the proposed model acknowledged that, in the context of social verification, the credibility of the organic products would be enhanced, and hybridization of the consensuses would mitigate the scalability issues.